Quenching and cooling, residual stress and distortion control - Canale, Lauralice de Campos Franceschini; Narazaki, Michiharu (ASTM International, 2010)
"Fifty-nine peer-review papers focus on various issues related to quenching and cooling, residual stress, and distortion control of ferrous and non-ferrous metals. Topics cover: Heat Transfer ; Modeling and Simulation ; Distortion and Residual Stresses ; Property Predictions ; Quenchants and Quenching ; Gas Quenching ; Hardenability ; Cooling Curve Analysis Methodologies ; Dilatometric Analysis."--Publisher's website
Keywords: Steel -- Quenching.; Steel -- Defects.; elektronické knihy; electronic books